2016
DOI: 10.1155/2016/1801795
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Structural and Optical Properties of Hydrothermally Synthesized Zn2SnO4 Nanoparticles

Abstract: Ternary oxide Zn2SnO4 has emerged as a promising material due to its tunable work function, band gap energy, and electric resistivity by simply varying the composition of the material. Zinc stannate nanoparticles were synthesized by green hydrothermal growth technique at 200°C for the reaction time of 24 h using stannic chloride pentahydrate (SnCl4·5H2O) and zinc chloride (ZnCl2) as precursors maintained at pH value of 8. X-ray diffraction analysis confirmed the phase purity and high crystalline nature of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…10b. [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] The electron affinity (w) of ZnO, SnO 2 , and Zn 2 SnO 4 has been found to be 4.20, 4.20, and 4.50 eV, respectively, 10,39,40,57,58 while the work functions (F) of ZnO, SnO 2 , and Zn 2 SnO 4 have been reported to be 4.71, 4.84, and 4.90 eV, respectively. [59][60][61][62][63][64] It shall be noted that the Fermi level inferred from the literature can only be used for qualitative discussion of oxygen vacancies.…”
Section: Proposed Sensing Mechanismmentioning
confidence: 99%
“…10b. [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] The electron affinity (w) of ZnO, SnO 2 , and Zn 2 SnO 4 has been found to be 4.20, 4.20, and 4.50 eV, respectively, 10,39,40,57,58 while the work functions (F) of ZnO, SnO 2 , and Zn 2 SnO 4 have been reported to be 4.71, 4.84, and 4.90 eV, respectively. [59][60][61][62][63][64] It shall be noted that the Fermi level inferred from the literature can only be used for qualitative discussion of oxygen vacancies.…”
Section: Proposed Sensing Mechanismmentioning
confidence: 99%
“…The estimated E opt values were 3.89 and 3.93 eV for the direct and indirect transitions respectively, which slightly higher than value of the band gap of bulk Zn 2 SnO 4 calculated by Dinesh et al (2016) [24] and be in agreement with that with those reported in literature such that estimated by Fakhrzad et al (2019) [25] (around 3.8 eV). This blue shift in E opt might be caused by quantum confinement effect resulting from the small size [32]. With the addition of the rare earth dopants as Dy 3+ , the band gap values decreased and reached to 2.80 eV for direct transition.…”
Section: Ft-ir Analysismentioning
confidence: 98%
“…[20] Numerous other reports on Zn 2 SnO 4 nanoparticles have been shown (Figure 1a), either using standard hydrothermal synthesis or solvothermal synthesis. [16,[21][22][23][24][25][26][27][28] Regarding ZnSnO 3 nanoparticles (Figure 1b), several hydro and solvothermal routes have been reported for its synthesis. [29][30][31][32] For instance, Beshkar et al reported the use of the Pechini method at 80°C to synthesize fcc-ZnSnO 3 nanoparticles, followed by a calcination at 700°C for 2 h. [33] Concerning 1D structures, while several reports on Zn 2 SnO 4 nanowires exist, these consist essentially in vapor phase methods, more specifically in thermal evaporation at high temperature (>750°C), [19] showing the difficulty in obtaining the stable phase of ZTO in the nanowire form.…”
Section: Hydrothermal Synthesis Of Zto Nanostructuresmentioning
confidence: 99%